EUPHEMISMS IN JORDAN KLEPPER’S SEGMENTS ON THE DAILY SHOW YOUTUBE CHANNEL: A SEMANTIC APPROACH - Delima Prastika (Universitas Negeri Medan, 2026)
This study aims to analyze euphemisms in Jordan Klepper's monologues on The Daily Show YouTube Channel using a semantic approach. This study analyzed transcripts from ten episodes broadcast between January and June 2025. The analysis process was carried out using a textual approach according to Smith (2017), and referring to the theory of types of euphemisms by Allan & Burridge (1991) and the theory of euphemism functions by Burridge (2012). The research found 34 euphemisms, divided into seven types. The most common type was